2020
DOI: 10.1111/jpn.13309
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cecotrophy on fat metabolism mediated by caecal microorganisms in New Zealand white rabbits

Abstract: Cecotrophy is a special behaviour of rabbits. Eating soft faeces can improve feed efficiency and maintain gut flora in rabbits. In our previous study, we found that fasting from soft faeces significantly reduced growth rate and total cholesterol (TC) in New Zealand white rabbits (NZW rabbits), thereby resulting in lower values for body weight and fat deposition in the soft faeces fasting group than in the control group. However, it has not been demonstrated whether cecotrophy by NZW rabbits can regulate lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…e maximum fat metabolism intensity is usually expressed as the percentage of maximum oxygen uptake, and there is a wide range (33%∼65%), which is mainly affected by factors such as exercise intensity, training level, body composition, gender, exercise style, and dietary supplement [13].…”
Section: Experiments and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…e maximum fat metabolism intensity is usually expressed as the percentage of maximum oxygen uptake, and there is a wide range (33%∼65%), which is mainly affected by factors such as exercise intensity, training level, body composition, gender, exercise style, and dietary supplement [13].…”
Section: Experiments and Researchmentioning
confidence: 99%
“…e fitness effect of College Students' fitness exercise prescription based on maximum fat metabolic intensity has not been reported. Next, take ordinary male and female college students as the research objects, measure their FAT max , formulate the exercise prescription of maximum fat metabolism intensity, study their fitness effect, and provide theoretical support for college students' fitness exercise [13].…”
Section: Experiments and Researchmentioning
confidence: 99%
“…SCFA plays a lipid-regulating role by up-regulating the gene of propionic acid fatty acid, inhibiting the activity of hepatic fat synthase and regulating the distribution of cholesterol in the blood and liver, thereby reducing serum triglyceride and cholesterol levels, helping to reduce fat synthesis and promote fat breakdown [ 24 , 25 ]. The microorganisms of Bacteroides improve the digestive efficiency in herbivores and animals [ 26 , 27 ]. Firmicutes is the main decomposer of intestinal saturated fatty acids [ 28 ], and its members help to produce enzymes involved in fermenting nutrients and potentially produce vitamin B, and contribute to better absorption of calories from food, eventually leading to obesity [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous research results of our research group showed that CP caused changes in microbiota in the cecal contents of rabbits, reduced lipid metabolism in the liver, and affected growth performance [40][41][42]. Song et al demonstrated the detrimental effect on the reproduction of the rabbit by preventing coprophagy with a main role for this response played by CTSB on the granulosa cells of the ovary [43].…”
Section: Introductionmentioning
confidence: 90%